2022
DOI: 10.1128/jvi.01251-21
|View full text |Cite
|
Sign up to set email alerts
|

Structurally Mapping Antigenic Epitopes of Adeno-associated Virus 9: Development of Antibody Escape Variants

Abstract: Adeno-associated viruses (AAV) serve as vectors for therapeutic gene delivery. AAV9 vectors have been FDA approved, as Zolgensma®, for the treatment of spinal muscular atrophy and is being evaluated in clinical trials for the treatment of neurotropic and musculotropic diseases. A major hurdle for AAV-mediated gene delivery is the presence of pre-existing neutralizing antibodies in 40 to 80% of the general population. These pre-existing antibodies can reduce therapeutic efficacy through viral neutralization, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 87 publications
0
14
0
Order By: Relevance
“…AAV vectors are a versatile platform with proven flexibility, 47 , 48 , 49 , 50 and our studies demonstrated the possibility for the development of AAV-based vaccines with desired characteristics by using precise modifications and rational design.…”
Section: Discussionmentioning
confidence: 71%
“…AAV vectors are a versatile platform with proven flexibility, 47 , 48 , 49 , 50 and our studies demonstrated the possibility for the development of AAV-based vaccines with desired characteristics by using precise modifications and rational design.…”
Section: Discussionmentioning
confidence: 71%
“…Libraries were created through saturation mutagenesis of the AAV9 capsid surface loop corresponding to amino acids (AA) 452–458 (VP1 subunit numbering). This region corresponds to variable region IV (VR-IV; red) of the capsid, which is the farthest radially protruding surface loop 24 , and plays a multifunctional role in AAV biology, including a neutralizing antibody binding site 25 , 26 as well as transduction efficiency and cell surface receptor binding, due to proximity to the 3-fold-symmetry axis of the AAV9 capsid 24 , 25 . Briefly, binding interactions of galactosylated glycans and AAVR with the AAV9 capsid are known to occur around the 3-fold axis.…”
Section: Resultsmentioning
confidence: 99%
“…Ongoing efforts to further understand other AAV.cc47 attributes also include assessment of antigenicity as determined by neutralizing antibody assays. It is important to note that the AAV9 VR-IV surface loop has been previously implicated as an immunodominant epitope in antibody recognition 25 , 26 . Assessment of the immunogenicity of AAV.cc47 compared to AAV9 will require a large NHP cohort in a separately designed study.…”
Section: Discussionmentioning
confidence: 99%
“…The subcellular localization signals for proteins are well-characterized and AGO2 specifically overexpressed in the mitochondria appears to protect the heart through preserving CYTB and mitochondrial homeostasis in diabetes. Meanwhile, the use of rAAVs as delivery vectors is safe, 83 as exemplified by the US Food and Drug Administration approval of Luxturna and Zolgensma. Therefore, delivery of exogenous AGO2 with a mitochondrial signal peptide by rAAV9 vector appeared to be a promising therapeutic strategy against diabetes-induced cardiac dysfunction.…”
Section: Discussionmentioning
confidence: 99%